Media Infrastructures and the Politics of Digital Time Essays on Hardwired Temporalities - Volmar, Axel; Stine, Kyle (Recursions, 2021)
Digital media everyday inscribe new patterns of time, promising instant communication, synchronous collaboration, intricate time management, and profound new advantages in speed. The essays in this volume reconsider these outward interfaces of convenience by calling attention to their supporting infrastructures, the networks of digital time that exert pressures of conformity and standardization on the temporalities of lived experience and have important ramifications for social relations, stratifications of power, practices of cooperation, and ways of life. Interdisciplinary in method and international in scope, the volume draws together insights from media and communication studies, cultural studies, and science and technology studies while staging an important encounter between two distinct approaches to the temporal patterning of media infrastructures, a North American strain emphasizing the social and cultural experiences of lived time and a European tradition, prominent especially in Germany, focusing on technological time and time-critical processes.